2017
DOI: 10.21037/jgo.2017.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine/nab-paclitaxel as second-line therapy following FOLFIRINOX in metastatic/advanced pancreatic cancer—retrospective analysis of response

Abstract: This study demonstrates a clinical benefit of second-line nPG. The study also suggests a possible use of CA19-9 to predict response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
6
29
1
Order By: Relevance
“…In this manner, while the therapeutic effect of CS on patients with UR-PC is investigated, progress of chemo(radio)therapy is remarkable, and FOLFIRINOX or GnP regimen is used as first-line chemotherapy for patients with UR-PC. 12,13,[24][25][26] Hackert et al 13 reported that patients with UR-PC who received FOLFIRINOX as NST had a higher conversion rate and a better prognosis than those received other regimen and they advocated that FOLFIRINOX should be first-line therapy for patients with UR-PC. As the antitumor effect of these regimens are very high, candidates for CS are expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, while the therapeutic effect of CS on patients with UR-PC is investigated, progress of chemo(radio)therapy is remarkable, and FOLFIRINOX or GnP regimen is used as first-line chemotherapy for patients with UR-PC. 12,13,[24][25][26] Hackert et al 13 reported that patients with UR-PC who received FOLFIRINOX as NST had a higher conversion rate and a better prognosis than those received other regimen and they advocated that FOLFIRINOX should be first-line therapy for patients with UR-PC. As the antitumor effect of these regimens are very high, candidates for CS are expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…When the combination of irinotecan, oxaliplatin, leucovorin and 5FU (FOLFIRINOX) regimen is given as a first line therapy, patient in good shape could be treated with a gemcitabine-based regimen. Reports have shown feasibility of this regimen [46,47], but there are no phase III trials supporting this recommendation. As a result, from first line chemotherapy toxicity and declined performance status, it is advisable to use an attenuated regimen in this situation, reducing doses or changing schedules to biweekly administration [48].…”
Section: Second-line Systemic Therapy For Metastatic or Local Advancementioning
confidence: 99%
“…Although there is no data from randomized, controlled studies to support this strategy, multiple single-institution, retrospective analyses suggest that gemcitabine/nab-paclitaxel is a reasonable second-line option following FOLFIRINOX. 22,23,24 …”
Section: Second-line Systemic Treatment For Advanced Pancreatic Cancermentioning
confidence: 99%